2020
DOI: 10.1021/acs.jpcc.0c04107
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure-Induced Structural and Chemical Transformations in NaN3

Abstract: Polynitrogen compounds have attracted great interest due to their potential application in the field of high-energy-density materials (HEDMs). Alkali azides are powerful candidates for the high-pressure preparation of HEDMs. In this work, we report a study of the crystal structure evolution and chemical transformation of NaN 3 under high pressure by in situ Raman spectroscopy and synchrotron X-ray diffraction methods up to 57.9 GPa. The initial rhombohedral NaN 3 transforms into the monoclinic C2/m-NaN 3 at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Recently, spectroscopy combined with XRD measurements and theoretical calculations have been successfully used to characterize the newly synthesized novel binary alkali pentazolate compounds under high‐pressure conditions. [ 44 ] Furthermore, multigrain analysis using synchrotron radiation was developed and applied to solve the crystal structure of a new high‐pressure phase. [ 45 ] These advanced techniques might help to identify the details of the newly synthesized high‐pressure P x N y .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, spectroscopy combined with XRD measurements and theoretical calculations have been successfully used to characterize the newly synthesized novel binary alkali pentazolate compounds under high‐pressure conditions. [ 44 ] Furthermore, multigrain analysis using synchrotron radiation was developed and applied to solve the crystal structure of a new high‐pressure phase. [ 45 ] These advanced techniques might help to identify the details of the newly synthesized high‐pressure P x N y .…”
Section: Resultsmentioning
confidence: 99%
“…Recently Zhou et al reported the formation of Cm-NaN 5 by room-temperature compression of NaN 3 . 30 The compound was identified in a three-phase mixture by comparison of the theoretically predicted lattice and the experimental powder pattern, but the structure refinement was not performed. We cannot exclude the formation of metastable Cm-NaN 5 in the experiments of Zhou et al: compression of the crystalline phases at low temperatures beyond their stability range often results in the formation of metastable materials.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
“…[ 28 ] The cyclo ‐N 5 − is a stable, aromatic, planar anion and has relatively large decomposition energy barrier of 117 kJ mol −1 , which shows the promise to obtain polynitrogen‐based HEDMs. In contrast to the extreme difficulty of isolating N 5 − at room conditions, studies have shown that N 5 − can be stabilized at high pressure in compounds such as LiN 5 , [ 29 ] NaN 5 , [ 30 ] CsN 5 , [ 31,32 ] MgN 10 , [ 33 ] and CuN 5 . [ 34 ] Moreover, N 5 3− is predicted to further aggregate and form higher oligomers or polymeric network in GaN 5 and GaN 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation